PENGARUH MOTIVASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KARIR DIMEDIASI KINERJA GURU (Studi Kasus Pada SMK Negeri Di Kabupaten Pati) - Suprapti, 11.52.02.0025 (Students Journal of Economic and Management, 2013)
The Â purpose of this research are : (1) To analist and describe the motivation that has some influence in teachers competition of SMK Negeri in Pati Regency. (2) To analist and to describe the head masterâs leadership that has an influence at teacher compention in SMK Negeri in Pati Regency, (3) To analist and to describe the influence of motivation at teacherâs carreer of SMK Negeri in Pati Regency, (4) To analist and to describe the influence of head masterâs leadership at teacherâs carreer at SMK Â Negeri in Pati Regency, (5) To analist and describe the influence of Teacherâs competention in carreer at SMK Negeri in Pati Regency. Â  This kind of research is the field research and use kuantitatif approach. The population in this research are the teacher of SMK Negeri in Pati Regency (265 teachers) with use purposive sampling method with caracteristic the lowest grade is D3 and they have worked at least 5 years. These objects is taken with Slovin Method that get 159 teachers as the objects of the research. Date analist tehnic uses doble linier analisys system, R2 analisys, F analisys, research inatrument analisys uses Validation Analisys, Reliabilitation Analisys, Clasic Asumtion Analisys, .hipotesis analisys uses t analisys and path analisys. Â  The result of the research show that : (1) Motivation has a positive influence to teacher competition of SMK Negeri in Pati Regency.(2) Head master Leadership has a positive influence to teacher competition of SMK Negeri in Pati Negeri in Pati Regency. (4) Headmaster Leadership has a positive influence to teacher carreer of SMK Negeri in Pati Regency. (5) Teacher competention has a positive influence to teacher carreer of SMK Negeri in Pati Regency. (6) Motivation influence is more efective toward teacher competention mediation than influence direct to the carreer. (7) Teacher competention mediate the influences of headmaster leadership to the carreer is more efective than direct to ther carreer. Â  Â  KeywordÂ Â  : Motivation,Â  HeadmasterÂ  Leadership, TeacherÂ  Competention,Â  and Carreer Â